Response activity of alveolar macrophages in pulmonary dysfunction caused by Leptospira infection - Marinho,M. (2008)
Leptopspirosis is a syndrome with different clinical manifestations including the most severe and often fatal forms of pulmonary disease of unknown etiology. Pulmonary injury during the inflammatory process has been associated with the excessive number of alveolar macrophages (AMs) and polymorphonuclear leukocytes stimulated in the lungs and with the production of reactive oxygen and nitrogen intermediates and other inflammatory mediators. The aim of the present work was to evaluate the cellular immune response of AMs or inflammatory cells of hamsters during leptospirosis. The activity of AMs was determined by measuring nitric oxide (NO) and protein production as well as inflammatory cell infiltration in bronchoalveolar lavage (BAL) fluid. Pulmonary activity during infection was monitored by measuring pH, pressure of oxygen (PaO2), and pressure of carbon dioxide (PaCO2) in blood samples. Cellular immune response and its role in the genesis of leptospirosis have been incriminated as the main causes of tissue and pulmonary injuries, which consequently lead to the pulmonary dysfunction in severe cases of leptospirosis. The present results show a low production of NO in both supernatant of alveolar macrophage culture and BAL. In the latter, protein production was high and constant, especially during acute infection. Total and differential cell count values were 2.5X10(6) on day 4; 7.3X10(6) on day 21; and 2.3X10(6) on day 28 after infection, with lymphocytes (84.04%) predominating over neutrophils (11.88%) and monocytes (4.07%). Arterial blood gas analysis showed pulmonary compromising along with the infectious process, as observed in parameter values (mean±SD) evidenced in the infected versus control group: PaO2 (60.47mmHg±8.7 vs. 90.09mmHg±9.18), PaCO2 (57.01mmHg±7.87 vs. 47.39mmHg±4.5) and pH (7.39±0.03 vs. 6.8±1.3). Results indicated that Leptospira infection in hamsters is a good experimental model to study leptospirosis. However, some of the immune parameters showed variations which might be associated with the animal species.